2020
DOI: 10.1002/iub.2436
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid‐gold nanoparticles enhance radiation‐induced cell death of human glioma U251 cells

Abstract: Glioblastoma multiforme (GBM) is among the most common adult brain tumors with invariably fatal character. Following the limited conventional therapies, almost all patients, however, presented with symptoms at the time of recurrence. It is dire to develop novel therapeutic strategies to improve the current treatment of GBM. Gallic acid is a well-established antioxidant, presenting a promising new selective anti-cancer drug, while gold nanoparticles (GNPs) can be developed as versatile nontoxic carriers for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Ga, a trihydroxybenzoic acid, has an anti-cancer effect against a variety of cancer cells. At great concentrations, Ga induces a diminution in mitochondrial antioxidant activity, inhibits cell proliferation and decreases the power to repair the destruction of glioma T98G and U251 cells [13,14]. Ga decreased the proliferation and induced apoptosis through the activation of p-38 signaling and the decrease in ERK1/2 and JNK signaling in osteosarcoma cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ga, a trihydroxybenzoic acid, has an anti-cancer effect against a variety of cancer cells. At great concentrations, Ga induces a diminution in mitochondrial antioxidant activity, inhibits cell proliferation and decreases the power to repair the destruction of glioma T98G and U251 cells [13,14]. Ga decreased the proliferation and induced apoptosis through the activation of p-38 signaling and the decrease in ERK1/2 and JNK signaling in osteosarcoma cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid (3,4,5‐trihydroxybenzoic acid, GA) is a well‐established antioxidant that shows potential anti-tumor capacity against GBM in vitro, however, the limited delivery method and poor drug availability restrict its further application. Through physical agitation adsorption, Zhou et al [ 117 ] constructed the GA@GNPs characterized with an average diameter of 23 ± 0.34 nm. The GA@GNPs system exhibited cytotoxic effect on GBM cells and sensitized the radiation‐mediated S and G2/M cell cycle arrest.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…GA exerts many beneficial properties such as antiinflammatory (BenSaad, Kim, Quah, Kim, & Shahimi, 2017), antioxidant (Yen, Duh, & Tsai, 2002), antifungal , and anticancer effects (Verma, Singh, & Mishra, 2013). Various studies have shown these anticancer effects in glioma (Jing et al, 2021;Lu et al, 2010;Musthafa et al, 2021). Paolini et al (2015) showed that cell viability and mitotic index of T98G glioma cells treated with different GA concentrations were reduced dose-dependently.…”
Section: Gallic Acidmentioning
confidence: 99%